Analysis of Interpersonal Communication Dynamics Among Adolescent Girls Experiencing Fatherlessness: A Phenomenological Study - Artadaya Muhammad Ramdhani; Ayu Larasati (CV Edujavare Publishing, 2026)
Fatherlessness is a significant issue in communication studies because the physical and emotional absence of a father figure may influence adolescent girls’ ability to build relationships, develop trust, and express emotions. This study analyzes the interpersonal communication dynamics of adolescent girls experiencing fatherlessness and explores the meanings they attach to their experiences. Using a qualitative phenomenological approach, the study involved five primary informants, one supporting informant, and one expert informant selected purposively. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman model. Data validity was ensured through source and technique triangulation. The findings reveal four major themes: selective self-disclosure, insecurity and fear of abandonment, the need for affection and emotional security, and the importance of supportive family and social environments. Fatherlessness does not eliminate communication abilities but shapes openness, trust, support-seeking, and relationship-building in contextual ways within their daily interpersonal communication experiences.